Acridocarpus taitensis (Malpighiaceae), a new species from Taita Hills in Kenya, Eastern Arc Mountains - Nyange, Mwadime; Ngumbau, Veronicah Mutele; Luke, Quentin (Phytotaxa, 2020)
Acridocarpus taitensis (Malpighiaceae), a new species collected from Taita Hills (Ngangao Forest fragment), Kenya, is described and illustrated. The new entity is similar to A. congestus, but is distinguished by its longer glandular leaves, with markedly impressed lateral veins on the adaxial leaf surfaces, smaller bracts, and fruits with the apex of the wings obtuse in shape. This species has previously been recorded as Acridocarpus sp. in the book Kenya, Trees & Shrubs and as Acridocarpus taxon A in the book Kenya, Trees, Shrubs & Lianas.